THE EFFECTIVENESS OF USING YOUTUBE VIDEO IN TEACHING AND LEARNING PROCESS: WRITING NARRATIVE FOR SEVENTH GRADE STUDENTS - Posma Imelda Putri Siahaan; Didik . Santoso; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2022)
Learning English is so important today in this era globalization and modern since English is an International Language. Nowadays, students are required to be able to understand and get to know English further, this is evidenced by the existence of English lesson in every school, from kindergarten to Senior High School. Because of the development of education, many of National schools adopt two language systems in teaching, namely bilingual language.  In Teaching English, especially narrative text, it is quite difficult, especially if we learnt seventh grade students whose age about eleven until twelve years old, as we know that, the age of 11 – 12 years old usually have a very high level of boredom, especially they learnt about text. As the teacher, we have to reduce their boredom and make the class more interactive. On the Interactive class, The students do not only listen or read a text from the textbook but also must be answer the question based on the text. From this observation, the writer want to compare about how if the technology nowadays will be combined in Teaching and Learning Process. This journal discusses about to find out whether the students’ interest in writing narrative taught by using text book is significantly higher than that taught by animated . The students would learn how to produce a narrative text (fable) by using textbook and watching in Video. From this observation, the writer found that using You Tube as a visual media is more effective in teaching narrative than using text book as a printed media in teaching media for seventh grade students, the class is more interactive by using a You Tube, it means that students can learn English especially how to speak fluently through the characters in the Video, and the teacher can be easier in providing an understanding of the meaning related on narrative text. Keywords: Writing Narrative , You Tube Video, Seventh Grade Students’ Interest